Enhancing non-invasive brain stimulation with non-invasively delivered nanoparticles for improving stroke recovery. (December 2022) - Hong, Y.; Wang, J.; Li, J.; Xu, Z.; Yang, X.; Bai, M.; Gong, P.; Xie, Y.; Zhang, X.; Xu, P.; Chen, X.; Li, R.; et al.
Abstract: Nanoparticles have great potential in remote neural stimulation with physical fields, but translation of these approaches to the medical arena faces enormous challenges, especially due to the use of highly invasive brain delivery of nanoparticles. Here we explore an alternative strategy through employing non-invasive brain delivery of nanoparticles. Non-invasive brain delivery of superparamagnetic iron oxide nanoparticles (SPIONs) in rats is performed by combining several complementary methods. The thus-delivered nanoparticles (called Tat-SPIONs) are found to enhance the neural stimulation effects of transcranial magnetic stimulation (TMS), a clinically-used non-invasive brain stimulation device, as analyzed by electrophysiological, biochemical, and behavioral experiments. In particular, ischemic stroke rats treated by non-invasively delivered Tat-SPIONs coupled with TMS show significant improvement in stroke recovery in terms of general health status, motor-sensory function, and cognitive function, compared to those treated by TMS alone. Importantly, mechanistic studies by experiments and numerical simulation suggest that the neural stimulation enhancement is mediated by neuroplasticity at least in part, is caused by a magnetoelectric rather than magnetothermal effect, and is generated primarily by those Tat-SPIONs associated with neurons' plasma membranes. This further implies that the excellent membrane-binding ability of Tat peptide is crucial for SPION-enhanced TMS. Tat-SPIONs exhibit minimal toxicity and neuroinflammation, and are clearable from major organs. The presented technology platform paves the way for medical applications of nanoparticles in remote brain stimulation with physical fields for stroke as well as other neurological disorders. Graphical abstract: Image 1 Highlights: Non-invasive brain stimulation is enhanced by non-invasively delivered nanoparticles. Enhancement is mediated by magneto-electric effect, not magneto-thermal effect. Enhancement is generated by cell membrane-associated nanoparticles.